Implications of the new MRI-based rectum definition according to the sigmoid take-off: multicentre cohort study. Issue 2 (3rd April 2023) - Burghgraef, Thijs A; Hol, Jeroen C; Rutgers, Marieke L; Brown, Gina; Hompes, Roel; Sietses, Colin; Consten, Esther C J; ,
Abstract: Background: The introduction of the sigmoid take-off definition might lead to a shift from rectal cancers to sigmoid cancers. The aim of this retrospective cohort study was to determine the clinical impact of the new definition. Methods: In this multicentre retrospective cohort study, patients were included if they underwent an elective, curative total mesorectal excision for non-metastasized rectal cancer between January 2015 and December 2017, were registered in the Dutch Colorectal Audit as having a rectal cancer according to the previous definition, and if MRI was available. All selected rectal cancer cases were reassessed using the sigmoid take-off definition. The primary outcome was the number of patients reassessed with a sigmoid cancer. Secondary outcomes included differences between the newly defined rectal and sigmoid cancer patients in treatment, perioperative results, and 3-year oncological outcomes (overall and disease-free survivals, and local and systemic recurrences). Results: Out of 1742 eligible patients, 1302 rectal cancer patients were included. Of these, 170 (13.1 per cent) were reclassified as having sigmoid cancer. Among these, 93 patients (54.7 per cent) would have been offered another adjuvant or neoadjuvant treatment according to the Dutch guideline. Patients with a sigmoid tumour after reassessment had a lower 30-day postoperative complication rate (33.5 versus 48.3 per cent, P < 0.001), lower reintervention rate (8.8 versus 17.4 per cent, P < 0.007), and a shorter length of stay (a median of 5 days (i.q.r. 4–7) versus a median of 6 days (i.q.r. 5–9), P < 0.001). Three-year oncological outcomes were comparable. Conclusion: Using the anatomical landmark of the sigmoid take-off, 13.1 per cent of the previously classified patients with rectal cancer had sigmoid cancer, and 54.7 per cent of these patients would have been treated differently with regard to neoadjuvant therapy or adjuvant therapy. Abstract : A total of 13.1 per cent of rectal cancer patients are defined as sigmoid cancer patients after reassessment using the MRI-based sigmoid take-off. These sigmoid cancer patients show significantly better postoperative outcomes compared with rectal cancer patients.